2020
DOI: 10.1021/acsnano.0c00088
|View full text |Cite|
|
Sign up to set email alerts
|

Twist Angle-Dependent Atomic Reconstruction and Moiré Patterns in Transition Metal Dichalcogenide Heterostructures

Abstract: Van der Waals layered materials, such as transition metal dichalcogenides (TMDs), are an exciting class of materials with weak interlayer bonding which enables one to create so-called van der Waals heterostructures (vdWH). 1 One promising attribute of vdWH is the ability to rotate the layers at arbitrary azimuthal angles relative to one another. Recent work has shown that control of the twist angle between layers can have a dramatic effect on vdWH properties, including the appearance of superconductivity, 2,3 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
245
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(274 citation statements)
references
References 44 publications
16
245
0
1
Order By: Relevance
“…The anharmonicity in the effective mass and interlayer coupling will be necessary for accurate comparison to experimental results, but the overall intuition for the moiré flat bands is unchanged. In addition, in-plane relaxations at small twist angles form domain-wall structures [46][47][48][49] and will cause the moiré potential to become independent of the twist angle [50]. This prevents the tuning of ω to arbitrarily small values, and will define a minimum possible bandwidth for the flat bands.…”
Section: B Flat Bands In Mosmentioning
confidence: 99%
“…The anharmonicity in the effective mass and interlayer coupling will be necessary for accurate comparison to experimental results, but the overall intuition for the moiré flat bands is unchanged. In addition, in-plane relaxations at small twist angles form domain-wall structures [46][47][48][49] and will cause the moiré potential to become independent of the twist angle [50]. This prevents the tuning of ω to arbitrarily small values, and will define a minimum possible bandwidth for the flat bands.…”
Section: B Flat Bands In Mosmentioning
confidence: 99%
“…Previous studies have found that the moiré pattern is obtained by rotating the angle of two atomic layers of 2D materials. 18 However, we found that the 2D material with a single layer of the wave shape structure can obtain moiré patterns at different incident angles. Fig.…”
Section: Geometry Structurementioning
confidence: 79%
“…17 Rosenberger et al studied the moiré pattern of a transition metal dichalcogenide heterostructure and found that the angle rotation is related. 18 Cao et al found that the superconducting properties of two layers of graphene were exhibited at specific angles (approximately 1.11). 19 Therefore, matching lattice strains of interlayer couplings and angle rotation of the two atomic layer heterojunctions will form a moiré pattern.…”
Section: Introductionmentioning
confidence: 99%
“…[ 30,33 ] Besides the AA and AB stacking with corresponding orientation angles of 0° and 60°, other specific orientation angles such as 30° can also be formed during the growth but with much lower chance and control, due to the required larger stacking energy. [ 34 ] The bright‐field optical images ( Figure a) show the triangular‐shaped WSe 2 atomic layers with different orientational angles with respect to each other. The number of layers can be preliminarily determined by the optical contrast and further verified by atomic force microscopy (AFM) and Raman spectroscopy measurements (Figures S3 and S4, Supporting Information).…”
Section: Figurementioning
confidence: 99%